Implementing health system and the new federalism in Somalia: challenges and opportunities - Said, Adam Sheikh; Kicha, Dmitry Ivanovich (Frontiers in Public Health, 2024)
In the 21st century, healthcare stands out as a formidable, contentious social responsibility for governments due to its high costs. This study delves into Somalia's healthcare system under Federal Government leadership, scrutinizing the complexities of health governance and financing. The Federal Government (FGS), along with governmental states (FMS) and regional authorities, collectively shoulder leadership and governance roles within Somalia's healthcare framework. Vital to resilient and inclusive development, the health sector holds a pivotal role. A strategic investment in healthcare not only drives substantial demographic dividends through enhanced life expectancy and reduced fertility rates, but also paves Somalia's trajectory toward progress. The Federal Government of Somalia confronts a multitude of challenges in its pursuit of effective healthcare implementation. A prominent obstacle lies in health financing. Somalia relies heavily on international and private sources for health support, primarily due to limited government revenue generation. This financial shortfall restrains the government's capacity to allocate ample funds for public services and critical investments, including healthcare. This paper sheds light on the present healthcare landscape in Somalia and expounds on the hurdles confronted by healthcare systems under federal governance. Moreover, it delves into the historical evolution of Somalia's healthcare system and the advent of new federalist principles. In doing so, this study comprehensively examines the dynamics of healthcare governance, financing, and historical progression in Somalia.